Effect of Aerobic Exercise on Selenium Level in Plasma - Kanakarajah, Sarmmila; Soetedjo, Nanny N. N. M.; Lesmana, Ronny (Universitas Padjadjaran, Indonesia)
Moderate and high aerobic exercises are the activities that can induce high oxidant. Demandof endogen and exogen antioxidant for neutralizing oxidant induced by exercise will playimportant role in maintaining body performance. Microtrace elements, such as selenium,may able to balance high oxidant formation. However, limited research and data have beencollected with regards to the exercise and selenium. Therefore, this research was conductedto investigate the effect of aerobic exercise on selenium level in plasma. An analytic studywith experimental method of data collection was performed from October -November 2016.17 male students with the age between 19-25 years old and without medically compromiseddisease from Universitas Padjadjaran, Jatinangor, were selected as subjects. Blood sampleswere taken pre- and post-aerobic exercise, i.e., brisk walking with the intensity of 4.5 mi/h.Selenium level in plasma was then examined by enzyme linked immunosorbent assay (ELISA)kit as selenium binding protein (SELENBP1). This study found that 11 (65%) subjectshad a decrease in their selenium plasma after exercise (3.1 ± 2.58 ng/ml), 5 (29%) subjectshad an increase in their selenium plasma after exercise (2.08 ± 2.8 ng/ml) and 1 (6%) subjecthad unchanged selenium (SELENBP1) plasma (1.4 ± 1.4 ng/ml) level. Effect of aerobicexercise on selenium level in plasma varied among individuals.Keywords: aerobic exercise, selenium, young adult